Analisis Kebutuhan Pengembangan Bahan Ajar Drama Berbasis Cerita Rakyat Banyumas: Analysis of the Needs for Developing Drama Teaching Materials Based on Banyumas Folk Tales - Nurul Lutfiyah; Memet Sudaryanto; Nia Ulfa Martha (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the need to develop drama teaching materials based on Banyumas folklore, as an effort to provide materials that are relevant to students' needs and characteristics. This study uses the Research and Development (R&D) method using the ADDIE model. The focus of the study is the needs analysis stage, the first part of the ADDIE development model. The population in this study was all high school students in the Purwokerto area who received drama material in Indonesian Language subjects. From this population, the study collected samples from two schools: SMAN 5 Purwokerto and SMAN 3 Purwokerto. The results showed that students had a positive perception of drama learning and gained meaningful learning experiences, especially in aspects of self-expression, social interaction, and mental strengthening. However, the available teaching materials remained general, did not cover the full range of drama theory, and did not include examples grounded in local culture. Students also indicated a need for more comprehensive teaching materials that cover affective, psychomotor, and cognitive aspects. Furthermore, students have a favorable view of Banyumas folktales as a learning resource, particularly because their geographical and cultural proximity makes it easier for them to understand the values and moral messages conveyed in these tales. These findings confirm the need to develop drama teaching materials based on Banyumas folktales to provide contextual, meaningful, and student-centered learning.